Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1051/forest/2010017
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor identity and competition influence tree growth in Scots pine, Siberian larch, and silver birch

Abstract: Abstract• Previous studies on competitive interactions among silver birch, Scots pine, and Siberian larch have not addressed the direct importance of the species identity of nearby competitors.• We examined the joint importance of competition and species identity, using subject trees with a high local abundance of a single dominant neighboring species. Interspecific neighbors influenced annual height increment, shoot length, and branch number per unit crown length, especially in Scots pine. Silver birch and Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…Several studies reported that the competition and growth of silver birch trees, and consequently their survival prospects, are strongly related to the identity of neighboring species (Kaitaniemi & Lintunen 2010, Jõgiste 2010, Hynynen et al 2011. Their findings are consistent with our results, in that including sp to the best nonspatial mortality model definitely improved its fit.…”
Section: Drivers Of Silver Birch Mortalitysupporting
confidence: 92%
“…Several studies reported that the competition and growth of silver birch trees, and consequently their survival prospects, are strongly related to the identity of neighboring species (Kaitaniemi & Lintunen 2010, Jõgiste 2010, Hynynen et al 2011. Their findings are consistent with our results, in that including sp to the best nonspatial mortality model definitely improved its fit.…”
Section: Drivers Of Silver Birch Mortalitysupporting
confidence: 92%
“…Despite the fact that the identity of neighbouring species is an important factor in the characterization of their competitive effects (Bella, 1971;Zhao et al, 2006;Kaitaniemi & Lintunen, 2010;Bošelá et al, 2013), no significant improvement appeared in recalculating the selected indices using Ellenberg's light values except for young trees. One possible explanation is that in our study plots about two-thirds of the trees analysed were birch with the same light factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Estonia, birch is the second most abundant tree species in terms of forest cover (31.2%) and the coverage is expanding (Yearbook of Forest, 2013). A few attempts have been made to study birch growth related to the negative interaction of tree competitive status in stands (Jõgiste, 1998;Prévosto et al, 1999;Andreassen & Tomter, 2003;Damgaard & Weiner, 2008;Kaitaniemi & Lintunen, 2010).…”
Section: Study Datamentioning
confidence: 99%
“…Competition among neighboring trees mainly depends on (1) the tree species; (2) the inter-tree distances formed by the overall spatial tree pattern in a forest stand; and (3) tree parameters like diameter at breast height (DBH), tree height, or crown projection area (CPA) [1][2][3][4]. The information needed to assess these aspects is much higher compared to data provided by large scale forest inventories, despite the fact that catalogues of key attributes surveyed in forest inventories have broadened and that modern survey networks were developed towards multi-purpose forest inventories [5][6][7].…”
Section: Introductionmentioning
confidence: 99%